A case report of steroid-refractory bullous pemphigoid induced by immune checkpoint inhibitor therapy - Guan, Shasha; Zhang, Linlin; Zhang, Junyan; Song, Wenjing; Zhong, Diansheng (Frontiers in Immunology, 2023)
The widespread use of immune checkpoint inhibitors in several malignancies has revealed new immune-related adverse events. Bullous pemphigoid (BP) is an antibody-driven autoimmune disease characterized by skin inflammation and fluid-filled bullae. Herein, a 69-year-old man with lung squamous cell carcinoma developed multiple vesicles and tense bullae 3 weeks after the initiation of a programmed death-1 (PD-1) inhibitor, pembrolizumab, and chemotherapy. Biopsy revealed a subepidermal bulla with lymphocytic and eosinophil infiltration, and immunohistochemical studies predominantly showed CD4+ cells, a few CD8+ cells, and the occasional CD20+ lymphocyte. The serum anti-BP180 antibody level, as well as the interleukin-6 and interleukin-10 levels, were elevated compared to the lower levels of tumor necrosis factor-α. Eosinophil levels were high and consistent with the development of blisters. A diagnosis of BP associated with PD-1 inhibitor therapy was made, and the Common Terminology Criteria for Adverse Events classification was grade 3. Immunotherapy was permanently discontinued, and the patient’s bullous lesions failed to react to high-dose systemic corticosteroids combined with minocycline and niacinamide. Intermittent blister recurrence occurred in 2 months, eventually improving with the administration of two courses of intravenous immunoglobulin. At 5 weeks of follow-up, the patient’s tumor was reduced on a computed tomographic scan. Despite stable BP treatment, however, he repeatedly developed complications due to the complexity of his underlying disease and could not be treated with anti-tumor therapy. Early recognition and management of serious immune-related bullous dermatologic toxicity are essential for patient safety.